Zydowskie miasto w Lublinie - Balaban, Majer, 1877-1943.; Henker, Karl Richard; Balaban, Majer, 1877-1943. (Lublin : Wydawn. FIS : M. Gacka, 1991)
This is a history of the Jewish community in Lublin up to 1918.
Includes bibliographical references.
Keywords: Jews -- Poland -- Lublin -- History; Lublin (Poland) -- History